Społeczeństwo poznańskie z perspektywy onimicznej – wstępna rekonstrukcja badawcza - Kołodziejczyk-Trawińska, Aneta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2009)
As yet, there have been no comprehensive study on the historical anthroponymy of Poznań and Great Poland. On the map of Poland this region constitutes a kind of terra incognita. The article presented is a part of the project whose objective is to compile names and surnames of the inhabitants of Great Poland. The conclusions included in the article have a character of a research reconnaissance and concern the 17th and 18th-century surnames of the inhabitants of the left-bank Poznań (the names have been excerpted from birth certificates of the parish of St. Adalbert). The article presents Polish surnames formed as a result of appellative nomination. Since the semantics of the derivative stems of the studied anthroponyms is tightly connected with the world of plants and animals as well as the material and cultural manifestations of the community described in the article, the people`s surnames have been divided into 4 groups according to: 1) external attributes, 2) psychic features, 3) interactions with the outer world, 4) position of a person in the society. The conclusions drawn on the basis of the analysis can be summarised as the following theses: 1) the material collected is semantically heterogeneous, 2) the reasons for choosing a particular name are not always obvious, 3) the material gathered only slightly reflects the cultural and linguistic specific character of the studied community, 4) the majority of appellatives motivating surnames belong to general Polish vocabulary.